Negosiasi Makna dalam Penyelesaian Konflik Interdepartemental: Studi Kasus Komunikasi Organisasi di PT Hania Natura Indonesia - Laode Aharuddin Kapege; Munawir . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Interdepartmental conflict is an organizational communication problem that may emerge from differences in information, interpretation, interests, and coordination mechanisms among work units. This study aims to analyze how interdepartmental communication operates in resolving conflict between the production and quality departments at PT Hania Natura Indonesia and to identify the communication mechanisms used to restore coordination among employees. This study employs a qualitative approach with a case study design. Data were obtained through in-depth interviews, observation, and documentation involving parties directly related to the conflict. Data analysis consisted of data condensation, data display, and conclusion drawing and verification. The case originated from a change in the net weight specification of a fullcream goat milk product from 27 grams to 23 grams, which was communicated directly by the quality manager to the production leader without adequate coordination with the relevant units. This condition generated different interpretations between the quality and production departments, resulting in rejected production outputs and subsequent rework involving the maintenance department. The findings indicate that the conflict was not solely caused by differences in interests but also by unclear communication channels, weak cross-departmental coordination, and differences in interpreting the specification change. Conflict resolution was conducted through direct dialogue, clarification among managers and team members, and the reconstruction of coordination mechanisms. The study demonstrates that structured and dialogic interdepartmental communication can function as both a preventive and corrective mechanism for managing organizational conflict.